Efficacy of dihydroartemisinin/piperaquine and artesunate monotherapy for the treatment of uncomplicated Plasmodium falciparum malaria in Central Vietnam. (21st May 2020) - Rovira-Vallbona, Eduard; Van Hong, Nguyen; Kattenberg, Johanna H; Huan, Ro Mah; Hien, Nguyen Thi Thu; Ngoc, Nguyen Thi Hong; Guetens, Pieter; Hieu, Nguyen Luong; Mai, Tran Tuyet; Duong, Nguyen Thi Thuy; Duong, Tran Thanh; Phuc, Bui Quang; et al.
Abstract: Background: Artemisinin-based combination therapies (ACTs) have significantly contributed to reduce Plasmodium falciparum malaria burden in Vietnam, but their efficacy is challenged by treatment failure of dihydroartemisinin/piperaquine ACT in Southern provinces. Objectives: To assess the efficacy of dihydroartemisinin/piperaquine for uncomplicated P. falciparum malaria in Gia Lai, Central Vietnam, and determine parasite resistance to artemisinin (ClinicalTrials.gov identifier NCT02604966). Methods: Sixty patients received either dihydroartemisinin/piperaquine (4 mg/kg/day, 3 days; n = 33) or artesunate monotherapy (4 mg/kg/day, 3 days; n = 27) followed by dihydroartemisinin/piperaquine (AS + DHA/PPQ). Clinical phenotypes were determined during a 42 day follow-up and analysed together with ex vivo susceptibility to antimalarials and molecular markers of drug resistance. Results: Day 3 positivity rate was significantly higher in the AS + DHA/PPQ arm compared with dihydroartemisinin/piperaquine (70.4% versus 39.4%, P = 0.016). Parasite clearance time was 95.2 h (AS + DHA/PPQ) versus 71.9 h (dihydroartemisinin/piperaquine, P = 0.063) and parasite clearance half-life was 7.4 h (AS + DHA/PPQ) versus 7.0 h (dihydroartemisinin/piperaquine, P = 0.140). Adequate clinical and parasitological response at Day 42 was 100% in both arms. By RT–qPCR, 36% (19/53) patients remained positive until Day 7. No recurrences were detected. kelch13 artemisinin resistance mutations were found in 87% (39/45) of isolates and 50% (20/40) were KEL1/C580Y. The piperaquine resistance marker plasmepsin-2 was duplicated in 10.4% (5/48). Isolates from Day 3-positive patients ( n = 18) had higher ex vivo survival rates to artemisinin compounds ( P < 0.048) and prevalence of kelch 13 mutations ( P = 0.005) than Day 3-negative patients ( n = 5). The WHO definition of artemisinin resistance was fulfilled in 60% (24/40) of cases. Conclusions: Although dihydroartemisinin/piperaquine remained effective to treat P. falciparum, the high Day 3 positivity rate and prevalence of KEL1 strains calls for continuous monitoring of dihydroartemisinin/piperaquine efficacy in Central Vietnam.